Can nutrition education mitigate the impacts of COVID‐19 on dietary quality? Cluster‐randomised controlled trial evidence in Myanmar's Central Dry Zone - Catherine Ragasa; Isabel Lambrecht; Kristi Mahrt; Hongdi Zhao; Zin Wai Aung; Jessica Scott (Wiley, 2021)
Abstract We evaluate the immediate impact of a nutrition and gender behaviour change communication on dietary quality in rural communities in Myanmar and assess whether the communication helped mitigate the effect of the COVID‐19 crisis on dietary quality. The intervention was designed and implemented as a cluster‐randomised controlled trial in which 15 villages received the intervention and 15 control villages did not. The intervention was implemented from June to October 2020. This paper provides an assessment of the intervention's impact on dietary quality based on the results of two phone surveys conducted in August and October 2020. Immediate impacts of the intervention indicate an improvement in women's dietary diversity scores by half a food group out of 10. At baseline, 44% of women were likely to have consumed inadequately diverse diets; results indicate that 6% (p‐value: 0.003, SE: 0.02) fewer sample women were likely to have consumed inadequately diverse diets. More women in treatment villages consumed pulses, nuts, eggs and Vitamin A‐rich foods daily than in control villages. In response to economic shocks related to COVID‐19, households in the treatment villages were less likely to reduce the quantity of meat and fish consumption than in control villages. The long‐term impacts of the intervention need to be continuously evaluated.